PENGARUH KARAKTERISTIK PEKERJAAN TERHADAP LOYALITAS KARYAWAN DIMEDIASI VERTICAL TRUST DAN PERCEIVED SUPERVISORY SUPPORT - Satria, Michael Made Dika; Putra, Made Surya (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.11.TAHUN.2023, 2023)
Every company will try to get quality human resources in order to support the effectiveness of the company's work in achieving the expected goals. The purpose of this study was to explain the effect of job characteristics on employee loyalty mediated by vertical trust and perceived supervisory support at the Tritunggal Tuka Credit Cooperative. This research was conducted at the Tritunggal Tuka Credit Cooperative. The sample size used in this study was 80 people with the method of determining the sample, namely saturated sampling. Collecting data using a questionnaire. Data were analyzed using PLS-based SEM analysis techniques. The results show that job characteristics have a significant positive effect on employee loyalty, job characteristics have a positive effect on vertical trust, job characteristics have a positive effect on perceived supervisory support, vertical trust mediates the effect of job characteristics on employee loyalty, and perceived supervisory support mediates the effect of job characteristics on loyalty. employee. Based on the results of this study, it is expected that the Tritunggal Tuka Credit Cooperative understands job characteristics, vertical trust, and perceived supervisory support that can affect employee loyalty.